The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1055/s-0042-115567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pericardiectomy on training- and myocardial infarction-induced left ventricular hypertrophy, chamber dimensions and gene expression

Abstract: The primary purpose of the study was to evaluate whether a pericardiectomy (PERI) alters training- or myocardial infarction (MI)-induced left ventricular hypertrophy (LVH), chamber geometry, gene expression and/or running performance. Mice were randomized into 6 groups: naïve control (CONT)-sedentary (Sed), CONT-trained (Tr), PERI-Sed, PERI-Tr, MI-Sed and MI-Tr. MI mice also received a pericardiectomy as part of the MI surgical procedure. 10 weeks of treadmill running resulted in enhanced running performance-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
3
4
0
Order By: Relevance
“…To the best of our knowledge, no previous study has examined the apoptosis signaling pathway in response to METH and HIIT. However, the results of the present study agree with those of Delfan et al [ 33 ], Lu et al [ 24 ], and Wolff et al [ 26 ]. Delfan et al [ 33 ] and Lu et al [ 24 ] suggested that HIIT reduces caspase-3 gene expression in rat models of diabetes and myocardial infarction.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To the best of our knowledge, no previous study has examined the apoptosis signaling pathway in response to METH and HIIT. However, the results of the present study agree with those of Delfan et al [ 33 ], Lu et al [ 24 ], and Wolff et al [ 26 ]. Delfan et al [ 33 ] and Lu et al [ 24 ] suggested that HIIT reduces caspase-3 gene expression in rat models of diabetes and myocardial infarction.…”
Section: Discussionsupporting
confidence: 93%
“…Delfan et al [ 33 ] and Lu et al [ 24 ] suggested that HIIT reduces caspase-3 gene expression in rat models of diabetes and myocardial infarction. Additionally, Wolff et al [ 26 ] showed that treadmill training (15° inclination and 22 m/min) increases the melusin mRNA concentration in myocardial infarction and pericardiectomy mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indicators of endurance training adaption suggest that our trained mice underwent sufficient training, because we report higher maximal running velocities as well as higher heart weight/ body weight for both sexes. Further, previous work from our group reports elevated citrate synthase activity in the quadriceps femoris of mice who underwent a similar training protocol [12]. Thus perhaps differences (physiological, psychological) exist between forced and voluntary exercise that explain the differences between males and females in our data.…”
Section: Discussionsupporting
confidence: 55%
“…An exhaustive exercise test was performed using a modified graded protocol as previously published [12,13]. Briefly, the test began at 15 m/min for the SED group and 20 m/min for TR group.…”
Section: Exhaustive Exercise Testmentioning
confidence: 99%